Motivation, practices and indicators of responsible tourism from tour operators' perspectives in Kinabalu Park - Tay Kai Xin (2015)
Responsible tourism emerges as an approach to tourism management, and its emphasises the responsibilites of tourism stakeholder in tourism industry, to take action to achieve sustainable tourism development. Tour operator is one of the important stakeholders to practise responsible tourism in tourism destination. It argues that a deep understanding of tour operators’ perspectives on motives and responsible tourism practices is vital in order to sustain a world heritage site, Kinabalu Park. This research seeks to understand the motives and practices of responsible tourism that are grounded in tour operators’ perspectives in Kinabalu Park. The research objectives are: (i) To define the responsible tourism and green tourism from tour operator respectively,(ii) To describe tour operators’ motives to practise responsible tourism in Kinabalu Park by extending the push-pull motivation theory, (iii) To understand the practices of responsible tourism by tour operator in Kinabalu Park, (iv) To identify the challenges and barriers faced by tour operators in practising responsible tourism in Kinabalu Park, and (v) To explore the responsible tourism indicators of Kinabalu Park from tour operators’ perspectives. An inductive qualitative research approach is adapted and data collection was conducted using in-depth interviews with 25 licensed tour operator who operate tour at Kinabalu Park in Kota Kinabalu, Sabah. The finding reveals that both of responsible and green tourism is related or complement each other. Responsible tourism is more on tourism operation, whereas green tourism is about nature. The motivators trigger tour operators to practise responsible tourism are mainly attributed to the push factors, which related to the intrinsic motives including organization benefits, to response customer demand, obligation and positive image; however, interestingly, there are two new discoveries from the primary data, namely own initiative and education and awareness from external sources. Pull factors are market trend and government role. The findings show that practices of responsible tourism are limited in Kinabalu Park by tour operators. This is because Kinabalu Park is under the management of local authority, namely Sabah Parks, tour operators are more likely to put the responsibility on Sabah Parks to practise responsible tourism in the site. The challenges that faced by tour operators include lack of commitment from multi-stakeholders, absence of awareness about responsible tourism, intensity of market competition, limited resources, and population pressure; and limited availability of green technology especially transportation. Most of the respondents agree that the role of government is playing significantly in creating awareness and education; and its role should take place in the tourism industry at first in promoting responsible tourism.The findings revealed 17 key indicators that can be used at Kinabalu Park and categorised into destination management, economic value, ecological and social and cultural. The current study benefits local authority to design the incentive strategies that able to motivate tour operator plays proactive role in responsible tourism practices at tourism destination. The local authority also suggested to make strategies that overcome the challenges and barriers of responsible tourism practices by taking tour operators’ perspectives into consideration. However, the study is limited to focus on tour operator solely rather than whole tourism stakeholders. It suggests for further study on other tourism stakeholder perspectives on responsible tourism practices in Kinabalu Park, especially local authority and the local community.